Clinical Experience With Elasticity Imaging in a Community‐Based Breast Center. (1st February 2013) - Destounis, Stamatia; Arieno, Andrea; Morgan, Renee; Murphy, Philip; Seifert, Posy; Somerville, Patricia; Young, Wende
Abstract : Objectives: The aim of this study was to evaluate compression elasticity imaging in combination with standard B‐mode imaging for assessment of benign versus malignant breast lesions and correlation with needle biopsy. Methods: Institutional Review Board approval was obtained, and patients were prospectively enrolled from 2007 to 2011. A total of 221 patients yielding 230 elastograms recommended for biopsy were the basis of this analysis. Information collected included patient demographics, lesion laterality and location, and needle biopsy method and results. The longest dimension of the lesion between B‐mode and elasticity imaging was measured, and an elasticity imaging/B mode ratio of 1.0 or greater was considered to represent malignancy; a ratio of less than 1.0 was benign. Statistical analysis included calculation of descriptive statistics and generation of figures. Results: Of the 230 biopsies performed, cancer was revealed in 100 cases (43.5%). One hundred thirty (56.5%) benign findings were observed. Of the 100 malignant lesions, 99 had an elasticity imaging/B‐mode ratio greater than or equal to 1.0 (99.0%). Of the 130 benign lesions, 119 had an elasticity imaging/B‐mode ratio of less than 1.0 (91.5%). These results indicate 99.0% (99 of 100) sensitivity and 91.5% (119 of 130) specificity. Furthermore, we found a positive predictive value of 90.0% (99 of 110) and a negative predictive value of 99.2% (119 of 120). Conclusions: In this study, elasticity imaging had high sensitivity for malignant and benign lesions. Elasticity imaging in the clinical setting may prove to be an additional tool that is helpful to the breast clinician for characterization of lesions as benign or malignant. At this time, we are continuing our data collection because additional research is still necessary.